Global estimates on the number of people blind or visually impaired by cataract: a meta-analysis from 2000 to 2020 - Pesudovs, Konrad; Jonas, Jost B. (Eye, 2024)
To estimate global and regional trends from 2000 to 2020 of the number of persons visually impaired by cataract and their proportion of the total number of vision-impaired individuals.